Analisis Retorika Aristoteles (Ethos, Pathos, dan Logos) Dalam Video Khutbah Idul Adha Ustad Abdul Somad “Harta Hanyalah Titipan, Sudahkah Kamu Berqurban?” - Sundari Sundari; Rhani Febria (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to describe the use of Aristotle's rhetoric including ethos, pathos, and logos in the video of Ustaz Abdul Somad's Eid al-Adha sermon entitled